Interactions between Growth Factors and Integrins: Latent Forms of Transforming Growth Factor-β Are Ligands for the Integrin αvβ1 - Munger, John S. (The American Society for Cell Biology, 1998)
The multipotential cytokine transforming growth factor-β (TGF-β) is secreted in a latent form. Latency results from the noncovalent association of TGF-β with its processed propeptide dimer, called the latency-associated peptide (LAP); the complex of the two proteins is termed the small latent complex. Disulfide bonding between LAP and latent TGF-β–binding protein (LTBP) produces the most common form of latent TGF-β, the large latent complex. The extracellular matrix (ECM) modulates the activity of TGF-β. LTBP and the LAP propeptides of TGF-β (isoforms 1 and 3), like many ECM proteins, contain the common integrin-binding sequence RGD. To increase our understanding of latent TGF-β function in the ECM, we determined whether latent TGF-β1 interacts with integrins. A549 cells adhered and spread on plastic coated with LAP, small latent complex, and large latent complex but not on LTBP-coated plastic. Adhesion was blocked by an RGD peptide, and cells were unable to attach to a mutant form of recombinant LAP lacking the RGD sequence. Adhesion was also blocked by mAbs to integrin subunits αv and β1. We purified LAP-binding integrins from extracts of A549 cells using LAP bound to Sepharose. αvβ1 eluted with EDTA. After purification in the presence of Mn(2+), a small amount of αvβ5 was also detected. A549 cells migrated equally on fibronectin- and LAP-coated surfaces; migration on LAP was αvβ1 dependent. These results establish αvβ1 as a LAP-β1 receptor. Interactions between latent TGF-β and αvβ1 may localize latent TGF-β to the surface of specific cells and may allow the TGF-β1 gene product to initiate signals by both TGF-β receptor and integrin pathways.